2018
DOI: 10.1002/chem.201803666
|View full text |Cite
|
Sign up to set email alerts
|

Metallo‐Organozymes with Specific Proteolytic Activity

Abstract: Metallopeptides that show efficiency and selectivity in peptide bond cleavage in water at room temperature and neutral conditions are presented. These small and versatile organozymes take advantage of metal-coordinating building blocks that are strategically positioned centrally in a peptide backbone or in a peptide macrocycle. This approach provided peptide-metal complexes with scaffolds capable of utilizing the peptide functionality for productive binding of fluorogenic FRET peptide substrates, subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…2D and S4 †). Derived from hydrolysis samples of peptides 1a and 2, MS/MS sequencing of the primary autocleavage fragment f0 (m/z = 666.8262 + and m/z = 644.3182 + , respectively) conrmed the identity of the respective C-terminal fragment sequence [Ab [16][17][18][19][20][21][22][23][24] ]Y*G (Fig. S7D and F †).…”
Section: Ab 14-24 Congeners Are Susceptible To Intrinsic Autohydrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…2D and S4 †). Derived from hydrolysis samples of peptides 1a and 2, MS/MS sequencing of the primary autocleavage fragment f0 (m/z = 666.8262 + and m/z = 644.3182 + , respectively) conrmed the identity of the respective C-terminal fragment sequence [Ab [16][17][18][19][20][21][22][23][24] ]Y*G (Fig. S7D and F †).…”
Section: Ab 14-24 Congeners Are Susceptible To Intrinsic Autohydrolysismentioning
confidence: 99%
“…To discern the cross-catalytic ability of the f0 fragment, we investigated seeding the ACR in Ab 1-28 with [Ab [16][17][18][19][20][21][22][23][24] ]-Y*G (f0(1a)). We screened several stock solutions of f0(1a) (100-300 mM and pH 7.6-8.2) for subsequent ACR activation (Table S1, † stock entries VIII & XII) upon dilution (pH 7.4-7.8).…”
Section: Cross-catalytic Acr Seeding In Ab 1-28mentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by metalloproteases that contain Lewis acid metals in their active sites, various metals were combined with suitable organic ligands to form chelating complexes with a high stability and versatile reactivity that can be used for protein hydrolysis among many other biomolecular transformations. , In the past decade, our group has developed polyoxometalates (POMs) as inorganic ligands for metal cations, where the molecular recognition ability of the POM scaffolds toward protein surfaces was combined with hydrolytically active Lewis acid metal cations (Ce­(IV), Zr­(IV), or Hf­(IV)) to catalyze peptide bond hydrolysis. Despite this promising proof of concept, the relatively low reactivity of classical transition metal complexes, prompted the development of nanozymes, i.e., nanomaterials with intrinsic enzyme-like properties. The rapid evolution and growing understanding of nanomaterials allow for the engineering of active centers that mimic those of natural enzymes, resulting in nanomaterials that could address current limitations of natural enzymes. , Despite the remarkable advances in the field, most nanozymes have been designed to exhibit redox activity, mimicking the oxidase/peroxidase family of enzymes. Nanozymes that mimic other types of enzymes, such as proteases, have seen substantially less development in comparison. In this regard, metal–organic frameworks (MOFs) have recently emerged as highly reactive and recyclable catalysts for protein hydrolysis. In particular, MOFs based on Zr­(IV) and Hf­(IV) metal-oxo clusters (MOCs) have been used as catalysts for an array of different biomolecular transformations, including peptide bond hydrolysis, where theoretical studies suggested that MOCs act as the catalytically active sites. ,,, …”
Section: Introductionmentioning
confidence: 99%